Optimal communication associated with lower risk of acute traumatic stress after lung cancer diagnosis - Hardardottir, Hronn; Aspelund, Thor; Zhu, Jianwei; Fall, Katja; Hauksdottir, Arna; Fang, Fang; Lu, Donghao; Janson, Christer; Jonsson, Steinn; Valdimarsdottir, Heiddis; Valdimarsdottir, Unnur A. (Supportive care in cancer, 2022)
Purpose The aim of this study was to assess the role of the patient’s background and perceived healthcare-related factors in symptoms of acute stress after lung cancer diagnosis. Methods The study population consisted of 89 individuals referred for diagnostic work-up at Landspitali National University Hospital in Iceland and subsequently diagnosed with lung cancer. Before diagnosis, the patients completed questionnaires on sociodemographic characteristics, pre-diagnostic distress (Hospital Anxiety and Depression Scale), social support, and resilience. At a median of 16 days after diagnosis, the patients reported symptoms of acute stress on the Impact of Event Scale-Revised (IES-R) and experience of communication and support from healthcare professionals and family during the diagnostic period. Results Patients were on average 68 years and 52% reported high levels of post-diagnostic acute stress (IES-R > 23) while 24% reported symptoms suggestive of clinical significance (IES-R > 32). Prior history of cancer ( β = 6.7, 95% CI: 0.1 to 13.3) and pre-diagnostic distress were associated with higher levels of post-diagnostic acute stress ( β = 8.8, 95% CI: 2.7 to 14.9), while high educational level ( β = − 7.9, 95% CI: − 14.8 to − 1.1) was associated with lower levels. Controlling for the abovementioned factors, the patients’ perception of optimal doctor-patient ( β = − 9.1, 95% CI: − 14.9 to − 3.3) and family communication ( β = − 8.6, 95% CI: − 14.3 to − 2.9) was inversely associated with levels of post-diagnostic acute stress after lung cancer diagnosis. Conclusions A high proportion of patients with newly diagnosed lung cancer experience high levels of acute traumatic stress of potential clinical significance. Efforts to improve doctor-patient and family communication may mitigate the risk of these adverse symptoms.